2022
DOI: 10.3390/ma15124112
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Bond Strength Testing in 3D-Printed Mineral Materials for Construction Applications

Abstract: There are no standards for testing the properties of 3D-printed materials; hence, the need to develop guidelines for implementing this type of experiment is necessary. The work concerns the development of a research methodology for interlayer bond strength evaluation in 3D-printed mineral materials. In additive manufactured construction elements, the bond strength is a significant factor as it determines the load-bearing capacity of the entire structural element. After we completed a literature review, the fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The redispersed polymer powders are selected among the most popular ones, in particular: vinyl ester of versatile acid (VEOVA), copolymer-vinyl acetateethylene (VAE), and polymer of vinyl acetate (PVA), the characteristics of which are given in Table 2. The main task in the study of suitability for 3D printer fine-grained concrete mixtures without coarse aggregate DSTU B V.2.7-43-96 (Ukrainian Standart) is to ensure their required shape when extruded from the printer head with the achievement of the specified structural strength, as well as the strength of adhesion between the layers without the formation of cracks and other defects [5,20,21]. Samples for determining the properties of mixtures were made using a laboratory 3D printer (Figure 1), the characteristics of which are given in [5].…”
Section: Methodsmentioning
confidence: 99%
“…The redispersed polymer powders are selected among the most popular ones, in particular: vinyl ester of versatile acid (VEOVA), copolymer-vinyl acetateethylene (VAE), and polymer of vinyl acetate (PVA), the characteristics of which are given in Table 2. The main task in the study of suitability for 3D printer fine-grained concrete mixtures without coarse aggregate DSTU B V.2.7-43-96 (Ukrainian Standart) is to ensure their required shape when extruded from the printer head with the achievement of the specified structural strength, as well as the strength of adhesion between the layers without the formation of cracks and other defects [5,20,21]. Samples for determining the properties of mixtures were made using a laboratory 3D printer (Figure 1), the characteristics of which are given in [5].…”
Section: Methodsmentioning
confidence: 99%
“…The utilization of AM technology is widespread in aerospace, electrical, and biomedical applications [4]. However, in areas such as architecture and the construction industry, its implementation is still limited [5,6]. One notable advantage of AM is its ability to reduce material waste and lead times, offering a flexible manufacturing approach.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when it comes to objects printed flat on the build plate, the mechanical behavior depends on the manufacturing raster angle 19,23,24 . This is because, by changing the manufacturing raster angle, the strength performance of the printed objects vary based on the average layer adhesion and the ultimate tensile strength of the 3D‐printed material 25,26 . Specifically, Weake et al 27 found that the tensile strength of an acrylonitrile butadiene styrene (ABS) part could be up to 150% higher when the applied force is parallel to the material filaments (manufacturing angle equals to 0°) than perpendicular (manufacturing angle equals to 90°).…”
Section: Introductionmentioning
confidence: 99%
“…In the former case, the overall strength is related to the axial strength of each material filament, whereas in the latter case, the overall strength only depends on the bonding forces between adjacent filaments 19 . Thus, by comparing the average layer adhesion 25 and the ultimate tensile strength of the material, 24 it is identified that parallel loading leads to larger overall tensile strength than perpendicular loading. As such, manufacturing angle is definitely worth of extra attention as far as the mechanical performance of a 3D‐printed object is concerned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation